In the Wnt of Paneth Cells: Immune-Epithelial Crosstalk in Small Intestinal Crohn’s Disease - Armbruster, Nicole S.; Stange, Eduard F.; Wehkamp, Jan (Frontiers in Immunology, 2017)
Paneth cells, specialized secretory epithelial cells of the small intestine play a pivotal role in host defense and regulation of microbiota by producing antimicrobial peptides especially -but not only- the human α-defensin 5 (HD5) and HD6. In small intestinal Crohn’s disease (CD) which is an entity of inflammatory bowel diseases, the expression of HD5 and HD6 is specifically compromised leading to a disturbed barrier and change in the microbial community. Different genetically driven but also non genetic defects associated with small intestinal CD affect different lines of antimicrobial Paneth cell functions. In this review we focus on the mechanisms and the crosstalk of Paneth cells and bone marrow derived cells and highlight recent studies about the role of the Wnt signaling pathway in this connection of ileal CD. In summary, different lines of investigations led by us but also now numerous other groups support and reconfirm the proposed classification of this disease entity as Paneth´s disease.